Serum lipid levels and the prevalence of dyslipidaemia among rural and urban Thai adults - Are the NCEP III guidelines appropriate? - Anushka Patel (2018)
The authors' objective was to describe the distribution of serum lipids and the prevalence of dyslipidaemia using US lipid-lowering guidelines in an adult Thai population. Fasting serum lipids were measured in a population-based survey that included 5305 rural and urban Thai adults aged 35 years. The US National Cholesterol Education Program (NCEP) guidelines were used to determine the eligibility of each individual for lipid-lowering therapy. Compared with urban residents, rural residents had lower mean levels of total cholesterol (men: 4.80 vs 5.54 mmol/L, women: 5.18 vs 5.71 mmol/L, both p < 0.001) and high density lipoprotein cholesterol (men: 1.06 vs 1.19 mmol/L, women: 1.13 vs 1.34 mmol/L, both p < 0.001). Mean triglyceride levels were higher in rural compared to urban populations, for both men (2.15 vs 1.88 mmol/L, p = 0.001) and women (1.73 vs 1.51 mmol/L, p = 0.01). Direct application of the NCEP guidelines identified up to 37% of the adult population (or 10 million adult Thais) as eligible for lipid-lowering drug therapy, which is an unfeasibly high proportion of the population. Urgent strategies are required to prevent increasing levels of dyslipidaemia in Thailand, as well as to develop and promulgate treatment guidelines that incorporate locally-relevant risk prediction functions.